PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL CONRAD NUSA DUA BALI - Sagung Mas Suryaniadi; Ni Nyoman Supiatni; Anak Agung Gede Bagus Arta Wiguna (STIMI Handayani Denpasar, 2021)
The progress of an organization is inseparable from the role of humans as activators of the organization. Human resources are crucial aspects to support the performance of a company in order to be able to survive in the current tight business competition. Therefore, a company must be able to manage its human resources well in order to improve performance in the company. Many factors that affect performance include work stress and work motivation. This study aims to determine the effect of work stress and work motivation on employee performance at the Conrad Hotel. The study was conducted with a total sample of 81 people. The sampling technique uses the Proportioned Stratified Random Sampling method. This research uses quantitative methods that use data from the results of questionnaire data processing. The analysis technique used is multiple linear regression. The results of this study indicate that work stress (X1) has a negative effect on performance with the regression coefficient value is -0.100 is negative and the significance value is 0.015. Work motivation (X2) has a positive effect on performance with a regression coefficient value of 0.447 and a significance value of 0.000. F test results show the value of F is 86.255 and the significance value is 0.000 this means that work stress and work motivation simultaneously affect performance with a percentage of 68.1% performance influenced by work stress and work motivation and 31.9% influenced by factors outside research